A Rectangular Planar Spiral Antenna for GIS Partial Discharge Detection. (5th June 2014) - Zhang, Xiaoxing; Han, Yefei; Li, Wei; Duan, Xuetao
Abstract : A rectangular planar spiral antenna sensor was designed for detecting the partial discharge in gas insulation substations (GIS). It can expediently receive electromagnetic waves leaked from basin-type insulators and can effectively suppress low frequency electromagnetic interference from the surrounding environment. Certain effective techniques such as rectangular spiral structure, bow-tie loading, and back cavity structure optimization during the antenna design process can miniaturize antenna size and optimize voltage standing wave ratio (VSWR) characteristics. Model calculation and experimental data measured in the laboratory show that the antenna possesses a good radiating performance and a multiband property when working in the ultrahigh frequency (UHF) band. A comparative study between characteristics of the designed antenna and the existing quasi-TEM horn antenna was made. Based on the GIS defect simulation equipment in the laboratory, partial discharge signals were detected by the designed antenna, the available quasi-TEM horn antenna, and the microstrip patch antenna, and the measurement results were compared.